Structured Professional Judgment to Assist the Evaluation and Safety Planning of Suicide Risk: The Risk of Suicide Protocol (RoSP) - Gray, Nicola S.; John, Ann; McKinnon, Aimee; Raybould, Stephanie; Knowles, James; Snowden, Robert J. (Frontiers in Psychiatry, 2021)
Background: The Risk of Suicide Protocol (RoSP) is a structured professional judgment (SPJ) scheme designed in line with NICE guidelines to improve clinicians' ability to evaluate and manage suicide risk. Aims: This study aimed to evaluate the efficacy of RoSP in two settings: (1) unexpected deaths of people in the community who were known to mental health services; and (2) an inpatient hospital specializing in the assessment and treatment of patients with personality disorder. Method: In Study 1, information from a database of unexpected deaths (N = 68) within an NHS health board was used to complete a RoSP assessment (blind to cause of death) and information from the Coroner's Court was used to assign people to suicide vs. natural causes/accidental death. In Study 2, patients (N = 62) were assessed on the RoSP upon admission to hospital and their self-injurious behaviors were recorded over the first 3 months of admission. Results: (1) Evaluations using RoSP were highly reliable in both samples (ICCs 0.93–0.98); (2) professional judgment based on the RoSP was predictive of completed suicide in the community sample (AUC = 0.83) and; (3) was predictive of both suicide attempts (AUC = 0.81) and all self-injurious behaviors (AUC = 0.80) for the inpatient sample. Conclusion: RoSP is a reliable and valid instrument for the structured clinical evaluation of suicide risk for use in inpatient psychiatric services and in community mental health services. RoSP's efficacy is comparable to well-established structured professional judgment instruments designed to predict other risk behavior (e.g., HCR-20 and the prediction of violence). The use of RoSP for the clinical evaluation of suicide risk and safety-planning provides a structure for meeting NICE guidelines for suicide prevention and is now evidence-based.